Elastic scattering of linearly polarized hard x-rays. (August 2015) - Blumenhagen, K-H; Gaßner, T; Gumberidze, A; Märtin, R; Schell, N; Spillmann, U; Trotsenko, S; Weber, G; Stöhlker, Th
Synopsis: We investigated the elastic scattering of linearly polarized 175-keV photons by a neutral gold target. The angular-differential scattering cross section and the linear polarization of the scattered radiation were measured.